(untitled) (Signifiances (Signifying), 2017)
STEELS postulates that the origins of the linguistic sign were both self-referential and vocomimetic. More precisely, vocal resonances accompanying bilaterally symmetrical, close-open movements of the jaw may have been recruited intersubjectively by Homo to refer back to the jaw and its anatomical region, before being mapped homologously to bilaterally symmetrical parts of the body located to each side of the median plane, or along it. I claim that this body-naming strategy, which may still be detectable submorphemically in certain PIE body-part words, involves key enactive concepts such as sense-making and embodiment, and neurophysiological phenomena such as mirror neuron systems.